2017
DOI: 10.1039/c6cp07236d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene flakes obtained by local electro-exfoliation of graphite with a STM tip

Abstract: Graphite surfaces can be manipulated by several methods to create graphene structures of different shapes and sizes. Scanning tunneling microscopy (STM) can be used to create these structures either through mechanical contact between the tip and the surface or through electro-exfoliation. In the latter, the mechanisms involved in the process of exfoliation at an applied voltage are not fully understood. Here, we show how a graphite surface can be locally exfoliated in a systematic manner by applying an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…This observed migration is different and slower than the previously reported high mobility of carbon nanostructures and graphene nanoakes on top of a graphitic substrate with weak interactions between nanostructures and substrate. 31,42,43 Previous experimental observations have shown a super uidic behavior of graphene nanoakes (GNF) even at temperatures as low as 5 K. 44 Similarly, theoretical calculations show a high diffusion coefficient of (6.7 AE 0.6) Â 10 À6 cm 2 s À1 for GNF on top of defect-free graphene substrates at 300 K. 43 This is consistent with our molecular dynamics studies (MD) at 1500 K, which also show fast diffusion of GNF on top of graphene (ESI Video S2 †). Considering this high mobility of GNF on top of graphene, it would not be possible to image this migration at high temperatures with our current exposure time of 1 s. However, in case of nanocrystalline graphene, the graphene substrate is highly defective and the defects limit diffusion by locally pinning GNFs.…”
Section: Resultsmentioning
confidence: 99%
“…This observed migration is different and slower than the previously reported high mobility of carbon nanostructures and graphene nanoakes on top of a graphitic substrate with weak interactions between nanostructures and substrate. 31,42,43 Previous experimental observations have shown a super uidic behavior of graphene nanoakes (GNF) even at temperatures as low as 5 K. 44 Similarly, theoretical calculations show a high diffusion coefficient of (6.7 AE 0.6) Â 10 À6 cm 2 s À1 for GNF on top of defect-free graphene substrates at 300 K. 43 This is consistent with our molecular dynamics studies (MD) at 1500 K, which also show fast diffusion of GNF on top of graphene (ESI Video S2 †). Considering this high mobility of GNF on top of graphene, it would not be possible to image this migration at high temperatures with our current exposure time of 1 s. However, in case of nanocrystalline graphene, the graphene substrate is highly defective and the defects limit diffusion by locally pinning GNFs.…”
Section: Resultsmentioning
confidence: 99%
“…by 7 V voltage ramp with sequential scanning, Fig. 19c, [102]) or to lithographically burn-out arbitrary shapes with nm precision (by continuous scanning in air with bias ! +2 V, Fig.…”
Section: Tip-induced Reactivitymentioning
confidence: 99%
“…b The use of corrals in HOPG for the confinement of tip-induced polymerization of diacetylene assemblies [96]. Direct exfoliation (c, [102]) and oxidative etching (d, [103]) of graphene layers with STM tip. a adapted with permission from [94] • AFM to determine film thickness (via mechanical scratching of grafted film), morphology and roughness; • STM to prove nanoscale arrangement of grafted species, to distinguish them from physisorbed impurities and for spatially controlled degrafting (see below); • XPS to prove chemical nature/integrity of functional groups (after grafting or any subsequent treatment of the grafts).…”
Section: Tip-induced Reactivitymentioning
confidence: 99%
“…Rubio-Verdú and colleagues showed that a scanning tunneling microscopy (STM) tip could be used to locally exfoliate HOPG by applying an electrostatic force at the edge of a terrace, forming triangular flakes [48]. Macroscopic exfoliation of graphite was demonstrated by Gao et al [49].…”
Section: Electrostatic Exfoliationmentioning
confidence: 99%